2013
DOI: 10.1186/1471-2474-14-143
|View full text |Cite
|
Sign up to set email alerts
|

Trends in knee arthroscopy and subsequent arthroplasty in an Australian population: a retrospective cohort study

Abstract: BackgroundKnee arthroscopy is a common procedure in orthopaedic surgery. In recent times the efficacy of this procedure has been questioned with a number of randomized controlled trials demonstrating a lack of effect in the treatment of osteoarthritis. Consequently, a number of trend studies have been conducted, exploring rates of knee arthroscopy and subsequent conversion to Total Knee Arthroplasty (TKA) with varying results. Progression to TKA is seen as an indicator of lack of effect of primary knee arthros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…30,31 In a large cohort study of 121,115 knee arthroscopies from Australia, 7.5% of all patients and 21.5% of patients >65 years old required conversion to total knee arthroplasty within 24 months of knee arthroscopy. 32 Before the introduction of new coding for cam decompression, pincer decompression, and labral repair in 2011, the most commonly coded procedure was CPT 29862 (chondroplasty/abrasion arthroplasty and/or debridement of labrum). However, it is unclear whether or not treatment of FAI and labral repair were coded as chondroplasty/abrasion arthroplasty before 2011.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In a large cohort study of 121,115 knee arthroscopies from Australia, 7.5% of all patients and 21.5% of patients >65 years old required conversion to total knee arthroplasty within 24 months of knee arthroscopy. 32 Before the introduction of new coding for cam decompression, pincer decompression, and labral repair in 2011, the most commonly coded procedure was CPT 29862 (chondroplasty/abrasion arthroplasty and/or debridement of labrum). However, it is unclear whether or not treatment of FAI and labral repair were coded as chondroplasty/abrasion arthroplasty before 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Our overall 2-year conversion to arthroplasty rate of less than 4% was much less than rates reported in other studies. Harris et al [8] reported a 2-year conversion rate greater than 20% in patients 65 years and older in Australia; however, the minimum age of patients in their study was older than that in our study and advanced age has been shown to be a risk factor for early conversion to arthroplasty [9,25]. Another study of patients in Ontario, Canada, showed a 1-year conversion rate of 9% and 3-year conversion rate of 18% among patients 50 and older [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies regarding the use of arthroscopic procedures for knee arthritis are inconsistent-some show decreasing use of arthroscopy with time [10,12,19], whereas another does not [1]. Some studies also show high rates of conversion from arthroscopy to arthroplasty within a short time, suggesting that the worst candidates for arthroscopy (ie, those with substantial enough degenerative changes to warrant knee arthroplasty) continue to be selected for the procedure [5,8,9,22,23]. Such findings raise concerns regarding the translation of evidence from major studies to real clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] For example, a placebo-controlled trial published in 2002, demonstrating a lack of effect of arthroscopic debridement, washout, or both for knee OA, 41 along with subsequent confirmatory studies, 44,45 has failed to consistently reduce arthroscopy rates for knee OA over the past decade. [46][47][48] Overall ambulatory arthroscopy rates in the USA actually increased by almost 50% between 1996 and 2006, 49 owing to a substantial increase in arthro scopy for meniscal tears, particularly among middle-aged patients, even though the value of arthroscopic debridement for degenerative meniscal tears in people with or without knee OA has also been questioned. [50][51][52][53][54] Several studies have demonstrated delays in the instigation of effective treatments for RA, despite the availability of evidence consistently supporting early intensive therapy.…”
Section: Increasing the Value Of Clinical Researchmentioning
confidence: 99%